DAMPAK KEGIATAN EKSTRAKURIKULER OLAHRAGA TERHADAP PEROLEHAN HASIL BELAJAR SISWA: Academic Achievement - Syamsudar, Bangbang (2012)
The purpose of this research is to understand the importance of sport and non sport extracurricular on school in order to optimize Junior High School students' academic achievement. This research employs quasi experimental design method with non equivalent control groups pre test post test design. Data is collected by using academic test on 3 subjects (PKn, Bahasa Indonesia, Matematika). Population of this research is all St. Mary Junior High School 7th grade Student class 2010-2011. Samples is taken by using total sampling. The total sample is 58 people. The samples were divided into three groups (students who attending sports extracurricular activities 3 times a week (21 people), students who attending sports extracurricular activities once a week (14 people), and students who attending non sports extracurricular activities (23 people)). All groups will run extracurricular activities for 6 weeks. Techniques of data analysis using two paired samples t test (pre-post test) and ANOVA test. The results of this study indicate that attending sports extracurricular activities 3 times a week, once a week, and non sport extracurricular activities have positive effect on students' academic achievement. Therefore, general conclusion from this study is that attending sports extracurricular activities 3 times a week are better than attending sports extracurricular activities once a week and non sports extracurricular activities in developing St. Mary Junior High School 7th grade students' academic achievement. This research suggests that students should attend well programmed extracurricular. Sports extracurricular activities should be conducted with frequency more than once a week and based on good training program. Meanwhile, non sports extracurricular activities program should be improved in order to enhance student's competences and skills.